Cognitive Radio and Networking for Heterogeneous Wireless Networks: Recent Advances and Visions for the Future - Di Benedetto, M.-G (Springer, 2015)
This book, written by leading experts from academia and industry, offers a condensed overview on hot topics among the Cognitive Radios and Networks scientific and industrial communities (including those considered within the framework of the European COST Action IC0902) and presents exciting visions for the future. Examples of the subjects considered include the design of new filter bank-based air interfaces for spectrum sharing, medium access control design protocols, the design of cloud-based radio access networks, an evolutionary vision for the development and deployment of cognitive TCP/IP, and regulations relevant to the development of a spectrum sharing market. The concluding chapter comprises a practical, hands-on tutorial for those interested in developing their own research test beds. By focusing on the most recent advances and future avenues, this book will assist researchers in understanding the current issues and solutions in Cognitive Radios and Networks designs.